2020
DOI: 10.1007/s11548-020-02238-4
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quality measurement of aortic contrast-enhanced CT angiographies for patient-specific dose optimization

Abstract: Purpose Iodine-containing contrast agent (CA) used in contrast-enhanced CT angiography (CTA) can pose a health risk for patients. A system that adjusts the frequently used standard CA dose for individual patients based on their clinical parameters can be useful. As basis the quality of the image contrast in CTA volumes has to be determined, especially to recognize excessive contrast induced by CA overdosing. However, a manual assessment with a ROI-based image contrast classification is a time-consuming step in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…1 . In order to generate the ground truth of the classification, we implemented a semiautomatic evaluation in previous works, 15 which evaluates the quality of the image contrast based on mean HU taken in regions of interest (ROI). This work establishes the subsequent classification.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 . In order to generate the ground truth of the classification, we implemented a semiautomatic evaluation in previous works, 15 which evaluates the quality of the image contrast based on mean HU taken in regions of interest (ROI). This work establishes the subsequent classification.…”
Section: Objectivesmentioning
confidence: 99%
“…In addition, radiologists have indicated which parameters are recorded routinely (rr). As a ground truth for the dose optimization in an earlier work 15 we implemented an image contrast quality measure similar to Behrendt et al 24 As shown in ►Fig. 2 under the guidance of radiological experts three ROIs were defined and placed in each CTA volume, respectively, in the aorta and the arteria femoralis communis.…”
Section: Clinical Study For Data Acquisitionmentioning
confidence: 99%
“…In total, the data set comprises 263 CTA images and the corresponding clinical parameters. The images were labeled as "excessive" based on the quality of their contrast [5][6][7]. Excessive means that the contrast is higher than necessary.…”
Section: Datamentioning
confidence: 99%
“…Excessive means that the contrast is higher than necessary. To determine this, the mean HU values of selected regions of interest were determined by a radiologist [6]. The data set includes CTA images of eight different recording protocols covering different body regions.…”
Section: Datamentioning
confidence: 99%
“…Reference slice selection: Baumgartner et al [9] described a real-time CNN-based fetal US slice selection method, focusing on the temporal aspect of the reference slice selection, which differ from our problem as there is more than one reference slice solution. Pallenberg et al [10] described a template-based spatial slice selection for CT.…”
Section: Fetal Brain Roi Detection and Segmentationmentioning
confidence: 99%